International retirement migration for Japanese retirees: Motivational push-pull factors and behavioral phenomena towards cultural assimilation - Rosli, Siti Hajar Binti (Turyzm/Tourism, 2024)
This article examines push and pull factors for Japanese retirees in Thailand as part of international retirement migration (IRM). Additionally, it studies levels of social integration, subjective wellbeing, life satisfaction, cultural assimilation and factors that hinder it. It examines the moderating and mediating effect of the relationship between independent and dependent variables. A quantitative method using a questionnaire was used and found that economic, health and social factors are significant in influencing retirees’ push and pull motivations. As for social integration, subjective well-being, life satisfaction and cultural assimilation, there is positive feedback from retirees. Factors that hinder cultural assimilation are language barriers and cultural differences. The results show a positive and strong association between language acquisition and social integration, between social integration and cultural assimilation, and between attitudes and cultural assimilation. There is a moderating effect between language acquisition and cultural assimilation. The results also show that there is no mediating effect for local support on the relationship between attitudes and social integration.